Joyful Learning with App-Based Interactive Quizzes in Senior High Schools in the Digital Era - Ashari, Muhammad Khakim; Rohmah, Annisa Nidaur; Yudi, Usman (CENDEKIA, 2023)
This study aims to identify the use of app-based interactive quizzes in joyful learning. This study uses a systematic literature review (SLR) approach. Reference sources came from journal articles and books relevant to the discussion obtained from portals or official journal indexing websites. After obtaining the articles, the next step is to tabulate them based on the main discussion in the writing that has been compiled. The data analysis technique in this research uses content analysis. The results of this study show that joyful learning is urgent to be applied in learning, in order to produce optimal, participatory, creative and fun learning. Joyful learning is the answer to various learning problems. The use of application platforms for interactive quizzes can be integrated in joyful learning. There are several applications that support this, including kahoot!, quizizz and wordwall. These three applications can be used in learning, especially for interactive quizzes, to see students' learning progress and evaluation, train critical thinking and provide a more meaningful learning experience for students. These applications also have diverse and interesting features so that they can be organized to be more friendly and certainly relevant to the digital era as it is today.